Young TPI: empowering animal-free science among the next- generation of scientists - G. Valverde, Marta; Abarkan, Fatima Zohra; Van Eijden, Rebecca; Menon, Julia M. L.; Gaio, Nikolas; Ramchandran, Aarti; De Leeuw, Victoria C. (Frontiers in Toxicology, 2025)
Strategies emphasizing animal-free innovation are imperative for the contemporary and future scientific research. They not only address important ethical concerns, but also should directly improve research accuracy and reliability through redirecting scientific inquiry toward more reliable and translatable methodologies. Promotion and encouragement for use of animal-free innovations among the next-generation of scientists, alongside knowledge acquisition and training in the increased capabilities of novel technologies, are fundamental for advancing science and the welfare of animals used for scientific purposes. The Dutch government has promoted initiatives such as Transitie Proefdiervrije Innovatie (TPI) to make the public aware of the current situation. However, the transition towards animal-free innovations will span over more than two generations. In this context, Young TPI emerged as the-first-of-its-kind network comprising young professionals and students dedicated to revolutionizing scientific practices by catalyzing the shift towards animal-free research. Grounded on three pillars - collaboration, awareness-raising, and networking - Young TPI has evolved into a premier youth network in the Netherlands. Boasting over 270 members spanning Dutch 49 institutions, including biotechnology startups and pharmaceutical companies and universities, Young TPI harnesses the diverse expertise of its members to propel a sustainable, future-proof transition and to promote a continuous dialogue with a wide range of stakeholders. This manuscript describes the conception, establishment, and progress of Young TPI from its start to present, detailing its strategy for communication, activities, and funding mechanisms, and ongoing endeavors to enlist new members and forge strategic alliances in pursuit of its mission.